PP.14.15: CARDIO-ANKLE VASCULAR INDEX (CAVI) DIFFERENTIATES PHARMACOLOGICAL PROPERTIES OF VASODILATORS NICARDIPINE AND NITROGLYCERIN IN ANESTHETIZED RABBIT. (June 2015) - Chiba, T.; Yamanaka, M.; Shimizu, K.; Takahashi, M.; Shirai, K.; Takahara, A.
Abstract : Objective: Vasodilators are clinically used in accordance with each pharmacological property. For example, Ca2+ channel blockers are prescribed for patients with hypertension, which dilate arterioles leading to reduction of peripheral vascular resistance. Organic nitrates are used for the treatment of various cardiovascular diseases including angina and heart failure to reduce ventricular preload and afterload, which dilates all segments of the vascular system from large conductance arteries to large veins. Since useful indexes reflecting vascular functions of larger conductance arteries are unavailable using non-invasive methods in contrast to the resistant arteries, we assessed whether the cardio-ankle vascular index (CAVI), established as a marker of arterial stiffness, could reflect different pharmacological actions of nicardipine and nitroglycerin on the systemic vasculature in anesthetized rabbits. Design and method: New Zealand White rabbits were anesthetized with halothane. The CAVI was calculated from the well-established basic equations obtained from the variables of brachial and tibial blood pressure and phonocardiogram. Results: Intravenous administration of nicardipine (1, 3 and 10 μg/kg) decreased the blood pressure, femoral arterial vascular resistance, and heart-ankle pulse wave velocity (haPWV) in a dose-dependent manner. Meanwhile, no significant change was detected in the CAVI at 1 and 3 μg/kg, which reflect the defining feature that CAVI is independent of blood pressure. At the highest dose of 10 μg/kg, the index increased. Intravenous administration of nitroglycerin (2, 4 and 8 μg/kg) also decreased the blood pressure, femoral arterial vascular resistance, and haPWV in a dose-dependent manner. Meanwhile, the CAVI decreased in a dose-dependent manner, which may reflect the pharmacological action that nitroglycerin dilates conductance arteries. Conclusions: These results suggest that CAVI is a useful index that can differentiate pharmacological properties of vasodilators nicardipine and nitroglycerin in anesthetized rabbit.